2011
DOI: 10.7150/jca.2.262
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Phenotypic Characterization of Canine Osteosarcoma Cell Lines

Abstract: Canine and human osteosarcoma (OSA) have many similarities, with the majority of reported cases occurring in the appendicular skeleton, gender predominance noted, high rate of metastasis at the time of presentation, and a lack of known etiology for this devastating disease. Due to poor understanding of the molecular mechanisms underlying OSA, we have characterized seven different OSA canine cell lines: Abrams, D17, Grey, Hughes, Ingles, Jarques, and Marisco and compared them to U2, a human OSA cell line, for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 23 publications
1
35
1
Order By: Relevance
“…These different cellular properties could be explained by the invasiveness and aggressive behaviour of D17 cell lines, derived from a metastatic lesion, as well as by the cellular phenotype acquired during the growth passages. 30 Histological investigation of D17 3D long-term cultures further showed the presence of vascular-like channels showing cavities in serial transversal sections surrounded by tumour endothelial-like cells identifiable using immunohistochemistry. As shown in results, the lack of CD31 expression excluded the ability of D17 cells to completely differentiate into endothelium in 3D cultures.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These different cellular properties could be explained by the invasiveness and aggressive behaviour of D17 cell lines, derived from a metastatic lesion, as well as by the cellular phenotype acquired during the growth passages. 30 Histological investigation of D17 3D long-term cultures further showed the presence of vascular-like channels showing cavities in serial transversal sections surrounded by tumour endothelial-like cells identifiable using immunohistochemistry. As shown in results, the lack of CD31 expression excluded the ability of D17 cells to completely differentiate into endothelium in 3D cultures.…”
Section: Discussionmentioning
confidence: 97%
“…Our study was firstly focused on two canine OSA cell lines (D17 and D22), revealing that D17 cell line showed a greater ability to grow in different conditions in comparison to D22 cell line or fibroblasts. These different cellular properties could be explained by the invasiveness and aggressive behaviour of D17 cell lines, derived from a metastatic lesion, as well as by the cellular phenotype acquired during the growth passages …”
Section: Discussionmentioning
confidence: 99%
“…The canine OSA cell lines Abrams, D17, Grey and Moresco were a gift from the Animal Cancer Center of Colorado State University (Fort Collins, CO, USA) (22,24). Cells were grown in minimal essential media (Invitrogen; Thermo Fisher Scientific, Inc., Waltham, MA, USA) supplemented with 10% (v/v) fetal bovine serum (FBS; Sigma-Aldrich, St. Louis, MO, USA) and 1% (v/v) Pen/Strep and fungizone solution (Invitrogen; Thermo Fisher Scientific, Inc.), and they were maintained in a tissue culture incubator at 37˚C in a 100% humidified atmosphere of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Thus suggesting high homology between the proteins of two species. Another study confirmed that the broadly used human antibody against ÎłH2AX is applicable in canine cells as well [41]. Although the MVC study is the only investigation of DDR initiation in canine cells, it: (i) implies similarities between human and canine response and (ii) represents an important starting point for exploring the impact of other stressors on canine cells.…”
Section: Discussionmentioning
confidence: 80%